Product development strategies in Yogyakarta’s Muslim fashion industry: Innovation and ethics - Putri, Nurul Elisa; Andriansyah, Yuli; Badjie, Fatou (Universitas Islam Indonesia, 2023)
IntroductionThe Muslim fashion industry has become a significant contributor to Indonesia’s creative economy, blending Islamic values with modern aesthetics to meet growing consumer demand. Yogyakarta, as a hub for small- and medium-sized enterprises in this sector, provides a unique context for exploring the interplay between innovation, market responsiveness, and adherence to Islamic principles.ObjectivesThis study investigates the product development strategies of Muslim fashion businesses in Yogyakarta, focusing on how they balance market demands with Islamic values. The research examines the practices of four businesses—Gamis Amika, Dafh Hijab, Koppi Holic, and Distro Gamis Nibras—and evaluates their alignment with ethical and religious principles.MethodUsing a qualitative approach, the study employs semi-structured interviews, field observations, and document analysis to collect data. A thematic analysis framework was applied to identify recurring patterns and insights into product design, digital marketing strategies, ethical practices, and the challenges faced by these businesses.ResultsThe findings reveal that businesses integrate customization, innovation, and traditional elements into their products to meet consumer preferences. Digital platforms, such as e-commerce and social media, play a critical role in expanding market reach. While all businesses align with Islamic principles in sourcing and pricing, smaller enterprises struggle with resource constraints and scalability.ImplicationsThe study underscores the importance of innovation and adherence to Islamic values in sustaining competitiveness in the Muslim fashion industry. It provides actionable recommendations for entrepreneurs and policymakers to address challenges such as market competition and resource limitations.Originality/NoveltyThis study contributes to the growing body of literature on Islamic business practices by highlighting the strategies and ethical considerations unique to the Muslim fashion industry. It offers insights into how businesses can navigate the balance between innovation and tradition to foster sustainable growth.